A Crude Bargain: Great Powers, Oil States, and Petro-Alignment. (20th October 2019) - Kim, Inwook
Abstract: Petro-alignment, a quid pro quo arrangement whereby great powers offer security in exchange for oil states' friendly oil policies, is a widely used and yet undertheorized energy security strategy. One consequential aspect of this exchange is that great powers choose different levels of security commitment to keep oil producers friendly. With what criteria do great powers rank oil states? How do we conceptualize different types of petro-alignments? What exactly do great powers and oil producers exchange under each petro-alignment type? I posit that a mix of market power and geostrategic location determines the strategic value and vulnerability of individual client oil states, which then generates four corresponding types of petro-alignment—security guarantee, strategic alignment, strategic favor, and neglect. Two carefully selected case comparisons—Saudi Arabia and Kuwait in 1970–91, and Azerbaijan and Ecuador in 1990–2013—show how great powers created, utilized, and maintained petro-alignments under the unique logic of oil markets and across varying geopolitical settings. The findings have important implications on great powers' grand strategies, strategic behaviors of oil states, and the role of oil in international security.